Interim positron emission tomography and clinical outcome in patients with early stage Hodgkin lymphoma treated with combined modality therapy. Issue 6 (June 2013) - Filippi, Andrea Riccardo; Botticella, Angela; Bellò, Marilena; Botto, Barbara; Castiglione, Anna; Gavarotti, Paolo; Gottardi, Daniela; Parvis, Guido; Bisi, Gianni; Levis, Alessandro; Vitolo, Umberto; Ricardi, Umberto
Abstract: The aim of the study was to investigate whether interim positron emission tomography (iPET) is prognostic in a cohort of patients with early stage Hodgkin lymphoma (HL) homogeneously treated with 3–4 cycles of ABVD (adriamycin, bleomycin, vinblastine and dacarbazine) followed by 30 Gy involved field radiotherapy. Eighty patients were selected (stage I–IIA HL, availability of iPET, minimum follow-up of 12 months), and after central review, 70 were judged negative (iPET−: 87.5%) and 10 positive (iPET+: 12.5%). The two groups were then analyzed for response, progression-free survival (PFS) and overall survival (OS). Only one out of 70 iPET− patients relapsed, with 69 in continuous complete remission (CCR). All 10 iPET + patients achieved a complete response and maintained persistent CCR at follow-up. The 3-year PFS and OS were, respectively, 97% and 98.4% for iPET− and 100% and 100% for iPET+ ( p = 0.63). iPET positivity does not seem to be a significant prognostic factor, and change in therapeutic strategy on the basis of iPET does not appear currently advisable outside clinical trials.